Digital Gap in Public Services to Support Development in the Coastal Area of Tangerang Regency - Toddy Aditya; Achmad Chumaedi (Universitas Hamzanwadi, 2024)
The purpose of this research is to find out how to overcome the digital divide to support the realization of public services in coastal areas in Tangerang Regency. Public services in the coastal areas of Tangerang Regency must be designed in a way that can meet the various needs of the community while maintaining sustainable development. Various sectors, such as health, education, transportation, and infrastructure, fall under this category of services. Innovation in public services is needed to improve the efficiency and accessibility of these services. These innovations can help people overcome various problems and improve their overall quality of life. The theories used in this study are the digital divide, public services and sustainable development. The method used in this study uses a quantitative approach, the primary data in this study is a questionnaire that is distributed directly and online, while the author's secondary data is taken from various trusted third-party sources. The population in this study is residents of the coastal area of Tangerang Regency, with a sample of 400 respondents. Meanwhile, the data processing tool that will be used in this study is SEM-PLS. The results of the study explain that to overcome the digital divide through improving digital infrastructure and technological literacy, as well as ensuring the inclusive and equitable implementation of SERVQUAL, it is very important to achieve sustainable development in Tangerang Regency.